Selective hydrogenation catalyst for C1-C3 fractions and preparation and application thereof

By using a bimodal pore distribution structure alumina support and microemulsion method to support Pd, Ni and Fe active components in the carbon dihydrogenation catalyst, the problem of inactivation caused by the catalyst's prone to green oil is solved, and the effect of improving catalyst selectivity and extending service life is achieved.

CN119680568AActive Publication Date: 2025-03-25PETROCHINA CO LTD
View PDF 21 Cites 0 Cited by

Patent Information

Application Number
CN202311242644.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-25
Publication Date
2025-03-25
Estimated Expiration
2043-09-25

AI Technical Summary

Technical Problem

The existing carbon dihydrogenation catalysts are prone to produce green oil during use, resulting in the deactivation of the catalyst and affecting its stability and selectivity.

Method used

Alumina with a bimodal pore distribution structure is used as a support, and active components such as Pd, Ni and Fe are supported by the microemulsion method to form two active centers to improve the activity and selectivity of the catalyst.

Benefits of technology

The anti-coking performance and selectivity of the catalyst are significantly improved, the service life of the catalyst is extended, and the cost of the catalyst is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004467910570000051
    Figure BDA0004467910570000051
  • Figure BDA0004467910570000061
    Figure BDA0004467910570000061
  • Figure BDA0004467910570000171
    Figure BDA0004467910570000171
Patent Text Reader

Abstract

The invention discloses a selective hydrogenation catalyst for C1-C3 fractions, a carrier of the catalyst has a bimodal pore distribution structure, and the catalyst at least contains Pd, Ni and Fe; wherein Pd is loaded by a microemulsion method and a solution method; ni is loaded by a microemulsion method; fe is loaded by a solution method; the total content of Pd loaded by the microemulsion method and the solution method is 0.009-0.0245% by taking the mass of the carrier as 100%, the content of Pd loaded by the solution method is 0.007-0.015%, and the ratio of Pd loaded by the solution method to Fe loaded by the solution method is (0.004-0.024): 1; the content of the Ni is 1.0 to 2.5 percent; the content of the Fe is 0.5 to 1.5 percent. The invention also discloses a preparation method and application thereof. According to the catalyst, the content of precious metal Pd is greatly reduced compared with that of a traditional catalyst, and the cost of the catalyst is effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a selective hydrogenation catalyst for C1-C3 fractions and its preparation and application. Background Art

[0002] Ethylene obtained by steam cracking of petroleum hydrocarbons (such as ethane, naphtha, diesel, hydrogenated tail oil, etc.) contains 0.2%-2.5% acetylene by mass. When used for polymerization, the acetylene in ethylene will reduce the activity of the polymerization catalyst and affect the physical properties of the polymer, so it must be removed. At present, the industry generally adopts the method of selective hydrogenation to remove acetylene, and the catalysts used are mainly precious metal catalysts such as Pd, Pt, and Au. In order to ensure that the ethylene generated by acetylene hydrogenation and the original ethylene in the raw material do not continue to hydrogenate to generate ethane, resulting in ethylene loss, it is necessary to ensure that the catalyst has a high hydrogenation selectivity in order to obtain better economic benefits.

[0003] According to the relative position of the C2 hydrogenation reactor and the demethanization, C2 hydrogenation is divided into pre-hydrogenation and post-hydrogenation. The C2 pre-hydrogenation reactor is before the demethanizer, and the hydrogenated materials generally contain C1, C2 fractions and C3 fractions. In addition to hydrogen and methane, the C1 fraction also contains CO. Generally, the material composition of pre-depropanization hydrogenation is: H2 15% ~ 30%, C2H6 4% ~ 10%, C2H4 25% ~ 40%, C2H2 0.4% ~ 0.7%, C3H6 8% ~ 11%, C3H8 1% ~ 2%, propyne 0.1% ~ 0.6%, propadiene 0.1% ~ 06%, CO 0.04% ~ 0.15%.

[0004] Noble metal catalysts have high activity, but are prone to generate green oil during use, causing the catalyst to coke and deactivate, affecting the catalyst stability and service life. CN200810119385.8 discloses a non-noble metal supported selective hydrogenation catalyst, comprising a carrier and a main active component and an auxiliary active component supported on the carrier, wherein the main active component is Ni, and the auxiliary active component is selected from at least one of Mo, La, Ag, Bi, Cu, Nd, Cs, Ce, Zn and Zr. The main active component and the auxiliary active component are both present in an amorphous form, with an average particle size of <10 nm. The catalyst is prepared by a microemulsification method, and its carrier is a non-oxidizing porous material.

[0005] The selective hydrogenation catalyst for alkynes and dienes is obtained by loading a noble metal such as palladium on a porous inorganic material carrier (US4762956). In order to increase the selectivity of the catalyst and reduce the catalyst deactivation caused by the green oil produced by the oligomerization reaction during hydrogenation, the prior art adopts a method of adding, for example, group IB elements as a co-catalyst component in the catalyst: Pd-Au (US4490481), Pd-Ag (US4404124), Pd-Cu (US3912789), or adding alkali metals or alkaline earth metals (US5488024), etc. The carriers used are aluminum oxide, silicon dioxide (US5856262), honeycomb philadelphite (CN1176291), etc. Patent US4404124 prepares a selective hydrogenation catalyst with a palladium shell distribution of the active component by a step-by-step impregnation method, which can be applied to the selective hydrogenation of carbon two and carbon three fractions to eliminate acetylene in ethylene and propyne and propadiene in propylene. US5587348 uses alumina as a carrier, adjusts the effect of silver and palladium as co-catalysts, and adds alkali metals and chemically bonded fluorine to prepare a carbon dihydrogenation catalyst with excellent performance. The catalyst has the characteristics of reducing green oil production, improving ethylene selectivity, and reducing the amount of oxygen-containing compounds produced. US5519566 discloses a method for preparing a silver and palladium catalyst by wet reduction, and prepares a silver and palladium two-component selective hydrogenation catalyst by adding an organic or inorganic reducing agent to the impregnation solution.

[0006] The above traditional carbon dihydrogenation catalysts are all prepared by impregnation method, and their active phases are Pd and Ag bimetallic. This method has the following disadvantages: (1) Affected by the pore structure of the carrier, the dispersion of active components cannot be precisely controlled and is highly random. (2) Affected by the surface tension and solvation effect of the impregnation liquid, the metal active component precursors are deposited on the carrier surface in the form of aggregates and cannot form a uniform distribution. (3) Carbon dihydrogenation has high requirements on catalyst selectivity. The traditional preparation method promotes the role of its auxiliary agent by increasing the amount of Ag, which leads to the obstruction of hydrogen transfer, the increase of the possibility of polymerization reaction, the increase of green oil production, and the impact on the life of the catalyst. The occurrence of the above three phenomena can easily lead to poor dispersion of metal active components, low reaction selectivity, and high green oil production, which in turn affects the overall performance of the catalyst.

[0007] ZL201110086174.0 forms a polymer coating layer on the surface of the carrier with a certain thickness by adsorbing a specific polymer compound on the carrier, and reacting the polymer with a compound with a functional group to make it have a functional group that can be complexed with the active component, and the active component undergoes a complexation reaction on the functional group on the surface of the carrier to ensure that the active component is orderly and highly dispersed. Using this patented method, the carrier adsorbs a specific polymer compound, and chemically adsorbs the polymer through the hydroxyl group of aluminum oxide. The amount of polymer compound adsorbed by the carrier will be limited by the number of hydroxyl groups of aluminum oxide; the complexation between the functionalized polymer and Pd is not strong, and sometimes the active component loading amount does not meet the requirements, and some active components remain in the impregnation solution, resulting in an increase in the cost of the catalyst.

[0008] In order to improve the anti-coking performance of the catalyst and reduce the surface coking degree of the catalyst, in recent years, a carbon two selective hydrogenation catalyst and preparation method using a bimodal pore carrier and a microemulsion method to load the active component have been disclosed. The selective hydrogenation catalyst disclosed in patent ZL201310114077.7 has a carrier mainly of alumina and a bimodal pore distribution structure, wherein the pore size of the small pores is within 50nm and the pore size of the large pores is 60-800nm. Taking the mass of the catalyst as 100%, the catalyst contains 0.01-0.5% by weight of Pd, which is a shell distribution with a thickness of 1-500um; it contains 0.2-5% by weight of Ni, and the anti-coking component Ni is controlled by a microemulsion method to control the particle size of the microemulsion to be larger than the particle size of the small pores of the carrier, so that Ni is mainly distributed in the large pores of the carrier. Patent ZL201310114079.6 discloses a preparation method for a hydrogenation catalyst, wherein the catalyst carrier is mainly alumina and has a bimodal pore distribution structure. The catalyst contains two active components, Pd and Ni. When preparing the catalyst, the anti-coking component Ni is introduced into the macropores of the carrier in the form of a microemulsion, and the active component Pd is mainly distributed on the surface of the carrier, especially in the small pores. Patent ZL201310114371.8 discloses a method for selective hydrogenation of carbon distillates suitable for pre-depropanization pre-hydrogenation process. The selective hydrogenation catalyst used in this method has a carrier of alumina or mainly alumina, and has a bimodal pore distribution structure, contains two active components Pd and Ni, and the anti-coking component Ni is mainly distributed in the macropores. The above method improves the anti-coking performance of the catalyst, but the single component Ni in the macropores of the catalyst carrier has a reduction temperature of more than 500°C. When reduced at this temperature, the catalyst active component Pd aggregates, which greatly reduces the catalyst activity. In order to compensate for the loss of catalyst activity, the amount of active component needs to be increased, which leads to a decrease in catalyst selectivity and a decrease in the utilization rate of active components.

[0009] Patent application ZL201910992442.1 discloses a catalyst with dual pore size distribution. Ni-Cu and Pd are distributed in the macropores. The catalyst is loaded by microemulsion method in two steps. Pd is loaded in the small pores. The selective hydrogenation reaction of acetylene is mainly carried out in the small pores. The byproducts generated in the reaction undergo saturated hydrogenation reaction in the Ni-Cu active center in the macropores. The coking rate of the catalyst is greatly reduced. However, the content of Pd, the main active component of the catalyst, is high, and the catalyst cost is high. Summary of the invention

[0010] The present invention aims to improve the selectivity of hydrogenation of C1-C3 fractions at a relatively low cost.

[0011] As one aspect of the present invention, it relates to a selective hydrogenation catalyst for C1-C3 fractions, the carrier of the catalyst has a bimodal pore distribution structure, and the catalyst contains at least Pd, Ni and Fe; wherein Pd is loaded by a microemulsion method and a solution method; Ni is loaded by a microemulsion method; Fe is loaded by a solution method; based on the mass of the carrier as 100%, the total content of Pd loaded by the microemulsion method and the solution method is 0.009-0.0245%, wherein the content of Pd loaded by the solution method is 0.007-0.015%, and the ratio of Pd loaded by the solution method to Fe loaded by the solution method is 0.004-0.024:1; the content of Ni is 1.0-2.5%; and the content of Fe is 0.5-1.5%.

[0012] In a specific embodiment, in the bimodal pore distribution structure, the pore size of the small pores is 30 to 80 nm, and the pore size of the large pores is 130 to 800 nm. In a specific embodiment, the specific surface area of ​​the catalyst is 3 to 15 m 2 / g.

[0013] As another aspect of the present invention, it relates to a method for preparing the selective hydrogenation catalyst of the above C1-C3 fraction, in which nickel and iron are first loaded, and then palladium is loaded. In a specific embodiment, nickel is loaded by a microemulsion method, iron is loaded by a solution method, and palladium is loaded by a microemulsion method and / or a solution method.

[0014] In a specific embodiment, the method comprises:

[0015] (1) adding the carrier to a Ni microemulsion for impregnation, calcining, and then adding an aqueous solution of an Fe precursor salt for impregnation and calcining; or, adding the carrier to an aqueous solution of an Fe precursor salt, calcining, and then adding the carrier to a Ni microemulsion for impregnation and calcining; the Ni microemulsion is formed by adding an oil phase, a surfactant, and a co-surfactant to an aqueous solution of a Ni precursor salt, and stirring, and the particle size of the microemulsion is greater than 80 nm and less than 800 nm;

[0016] (2) adding the product prepared in step (1) to an aqueous solution of a Pd precursor salt, aging, drying, and calcining, and then adding a Pd microemulsion for impregnation and calcining; or, adding the product prepared in step (1) to a Pd microemulsion for impregnation and calcining, and then adding it to an aqueous solution of a Pd precursor salt for aging, drying, and calcining; the Pd microemulsion is formed by adding an oil phase, a surfactant, and a co-surfactant to an aqueous solution of a Pd precursor salt and stirring, and the particle size of the microemulsion is greater than 80 nm and less than 800 nm.

[0017] In step (1) and step (2), the mass ratio of water in the aqueous solution to the oil phase is 2.5-4.5:1; the mass ratio of the surfactant to the oil phase is 0.1-0.4:1; and the mass ratio of the surfactant to the co-surfactant is 1.0-1.40:1.

[0018] In step (1), the oil phase is alkane, the surfactant is Triton X-100 or CTAB, and the cosurfactant is alcohol. Further, in step (1), the oil phase is cyclohexane or n-hexane, and the cosurfactant is n-butanol, n-pentanol or n-octanol.

[0019] In step (2), the oil phase is alkane, the surfactant is Triton X-100 or CTAB, and the cosurfactant is alcohol. Furthermore, in step (2), the oil phase is cyclohexane or n-hexane, and the cosurfactant is n-butanol, n-pentanol or n-octanol.

[0020] For the convenience of implementation, the Fe, Ni and Pd precursor salts should all be soluble salts.

[0021] The calcination temperature in step (1) is 400-600°C.

[0022] The calcination temperature in step (2) is 250-600°C.

[0023] The inventors found that in the catalyst of the present invention, two active centers are formed, one of which is the alkyne selective hydrogenation active center formed by Fe / Pd; the other is the byproduct hydrogenation active center formed by Ni / Pd, which is beneficial to improve the catalyst activity and selectivity. In order to reduce the cost of the catalytic reaction, the inventors considered using low-valent metals to replace the precious metals in the catalyst, but found that after replacing the precious metals with low-valent metal Fe, the catalytic activity was significantly reduced, and the catalytic reaction needed to be carried out at a higher temperature, resulting in ethylene being easily polymerized at high temperatures. Finally, the inventors found that after loading iron, a small amount of palladium was loaded, which could greatly improve the activity of the iron active center. Compared with traditional catalysts, it not only reduced the catalyst cost, but also did not significantly reduce its activity. . It is speculated that the reason may be that palladium has a higher hydrogen adsorption effect, which can realize the transfer of hydrogen from palladium atoms to the iron active center, thereby improving the activity of the iron active center.

[0024] As another aspect of the present invention, it relates to a carbon 2 hydrogenation process, using the above-mentioned C1-C3 fraction selective hydrogenation catalyst. The reduction temperature of the catalyst of the present invention is preferably 180-220°C.

[0025] The catalyst of the present invention can reduce the precious metal Pd content by up to 70% compared with the traditional catalyst, which is greatly reduced, and the catalyst cost is effectively reduced. Since the adsorption strength of non-precious metal Fe to CO is weaker than that of precious metal Pd, the catalyst of the present invention is less sensitive to changes in CO and can adapt to working conditions where the CO content changes greatly.

[0026] The operation cycle of the catalyst of the present invention is greatly extended. At the beginning of the hydrogenation reaction, the selective hydrogenation reaction of acetylene mainly occurs in the small pores. As the catalyst operation time increases, a portion of byproducts with larger molecular weights are generated on the catalyst surface. Due to their larger molecular size, these substances enter the large pores more and stay there for a longer time. Under the action of the nickel catalyst, double bond hydrogenation reactions occur to generate saturated hydrocarbons or aromatic hydrocarbons without isolated double bonds, and no substances with larger molecular weights are generated.

[0027] The catalyst of the present invention effectively reduces the catalyst cost. Conventional catalysts use Pd as the main active component for selective hydrogenation, and its content is generally about 0.03%. Among the catalyst costs, the cost of precious metals accounts for more than 60% of the total catalyst cost. In the present invention, the original precious metal is replaced by non-precious metal Fe, and the precious metal Pd becomes the auxiliary active component for selective hydrogenation, and its amount is up to 1 / 2 of that of conventional catalysts. Therefore, the catalyst cost is greatly reduced.

[0028] The catalyst of the present invention improves the ability of the catalyst to resist CO fluctuations. In traditional catalysts, the outer D orbital of Pd is completely empty, and the lone pair of electrons of CO can easily enter the empty orbital of Pd, while the outer P orbital of Fe atoms is half full, and the lone pair of electrons of CO cannot easily enter its orbit, so that the adsorption strength of CO on Fe atoms is weaker than that of the precious metal Pd, and thus the sensitivity to CO changes is reduced. Because the ability to resist CO fluctuations is better, it can adapt to working conditions where the CO content changes greatly. Compared with traditional catalysts, the catalyst of the present invention reduces the catalyst cost, prolongs the catalyst life, and improves the ability of the catalyst to resist CO fluctuations. DETAILED DESCRIPTION

[0029] Hereinafter, the technical solution of using iron to partially replace palladium to prepare a selective hydrogenation catalyst according to the present invention is described in detail through specific examples.

[0030] Source of raw materials or equipment:

[0031]

[0032] Sources of reagents and raw materials:

[0033]

[0034] Evaluation and analysis methods:

[0035] Analytical test methods:

[0036] Specific table: GB / T-5816;

[0037] Pore ​​volume: GB / T-5816;

[0038] Content of active components in catalyst: atomic absorption method;

[0039] Microemulsion particle size distribution of Ni / Cu alloy: Dynamic light scattering particle size analyzer, analyzed on M286572 dynamic light scattering analyzer;

[0040] The conversion rate and selectivity in the embodiment are calculated according to the following formula:

[0041] Acetylene conversion rate (%) = 100 × △ acetylene / inlet acetylene content

[0042] Ethylene selectivity (%) = 100 × △ ethylene / △ acetylene

[0043] Example 1

[0044] Carrier: A commercially available bimodal pore distribution spherical alumina carrier with a diameter of 4 mm, calcined at 1350°C, with a specific surface area of ​​3 m 2 / g, water absorption rate 35%, small pore diameter 55-80nm, large pore diameter 500-800nm, weigh 100g of the carrier. The calcination temperature and carrier physical properties are shown in Table 3.

[0045] Catalyst preparation:

[0046] (1) Weigh 3.11 g of nickel nitrate, dissolve it in 40 ml of deionized water, add 8.88 g of cyclohexane, 0.89 g of Triton X-100, and 0.64 of n-butanol, stir thoroughly to form a microemulsion, and impregnate 100 g of the carrier into the prepared microemulsion. After the emulsion is completely absorbed, dry it at 60° C. and calcine it at 600° C. for 5 h to obtain a semi-finished catalyst A.

[0047] (2) Weigh 4.36 g of ferric nitrate and dissolve it in 35 g of deionized water, then add the semi-finished catalyst A to the Fe salt solution, and after the solution is completely absorbed, age it for 4 hours, dry it at 120° C., and calcine it at 250° C. for 6 hours to obtain the semi-finished catalyst B;

[0048] (3) Weigh 11.67 mg of palladium chloride and dissolve it in 35 g of deionized water, adjust the pH to 1.5, then add the semi-finished catalyst B to the Pd salt solution, age it for 10 hours, dry it at 120° C., and calcine it at 500° C. for 4 hours to obtain a semi-finished catalyst C;

[0049] (4) Weigh 3.33 mg of palladium chloride and dissolve it in 40 ml of deionized water. Add 8.88 g of cyclohexane, 0.89 g of Triton X-100, and 0.64 of n-butanol. Stir thoroughly to form a microemulsion. Impregnate the semi-finished catalyst C into the prepared microemulsion. After the emulsion is completely absorbed, dry it at 60° C. for 6 hours and calcine it at 550° C. for 4 hours to obtain the desired catalyst.

[0050] The particle size of the microemulsion prepared in steps (1) and (4) was 800 nm as measured by dynamic light scattering.

[0051] The prepared catalyst was measured by atomic absorption spectrometry, and calculated based on the carrier as 100%, in Example 1, the Pd content was 0.009%, the Ni content was 1%, and the Fe content was 1%. The Pd content loaded by the solution method was 0.007%, and the Pd content loaded by the emulsion method was 0.002%.

[0052] Before use, it was placed in a fixed bed reaction device and reduced with a mixed gas with a molar ratio of N2:H2=1:1 at 220°C for 12 hours.

[0053] Comparative Example 1 provides a catalyst, the carrier of which is the same as that of Example 1, and Ni is not loaded in Comparative Example 1.

[0054] Catalyst preparation:

[0055] (1) Weigh 4.36 g of ferric nitrate and dissolve it in 35 g of deionized water. Then add the semi-finished catalyst A to the Fe salt solution. After the solution is completely absorbed, age it for 4 hours, dry it at 120° C., and calcine it at 250° C. for 6 hours to obtain the semi-finished catalyst A1.

[0056] (2) Weigh 11.67 mg of palladium chloride and dissolve it in 35 g of deionized water, adjust the pH to 1.5, then add the semi-finished catalyst B into the Pd salt solution, age it for 10 hours, dry it at 120° C., and calcine it at 500° C. for 4 hours to obtain the semi-finished catalyst B;

[0057] (3) Weigh 3.33 mg of palladium chloride and dissolve it in 40 ml of deionized water. Add 8.88 g of cyclohexane, 0.89 g of Triton X-100, and 0.64 g of n-butanol. Stir thoroughly to form a microemulsion. Dip the semi-finished catalyst C into the prepared microemulsion. After the emulsion is completely absorbed, dry it at 60°C for 6 hours and calcine it at 550°C for 4 hours to obtain the desired catalyst.

[0058] The particle size of the microemulsion prepared in step (3) was 800 nm as measured by dynamic light scattering.

[0059] The prepared catalyst was measured by atomic absorption spectrometry, and calculated based on the carrier as 100%, in Example 1, the Pd content was 0.009%, and the Fe content was 1%. The Pd content of the solution method was 0.007%, and the Pd content of the emulsion method was 0.002%.

[0060] Before use, it was placed in a fixed bed reaction device and reduced with a mixed gas with a molar ratio of N2:H2=1:1 at 220°C for 12 hours.

[0061] Example 2 This example provides a catalyst, the carrier of which is a commercially available bimodal pore distribution spherical carrier with a diameter of 4 mm and a composition of 90% alumina and 10% titanium oxide. After calcination at 1310°C, the specific surface area is 10 m 2 / g, water absorption rate 45%, small pore diameter 45-65nm, large pore diameter 260-620nm, weigh 100g of the carrier.

[0062] Catalyst preparation:

[0063] (1) Weigh 2.33 g of ferric chloride and dissolve it in 45 g of deionized water. Add 100 g of the calcined carrier to the prepared Fe salt solution. After the solution is completely absorbed, age it for 4 hours, dry it at 100° C., and calcine it at 500° C. for 6 hours to obtain a semi-finished catalyst D.

[0064] (2) 3.54 g of nickel chloride was dissolved in 45 ml of deionized water, and 15.52 g of n-hexane, 4.66 g of CTAB, and 3.88 g of n-pentanol were added and stirred thoroughly to form a microemulsion. The semi-finished catalyst D was impregnated into the prepared microemulsion, and after the emulsion was completely absorbed, it was dried at 100° C. and calcined at 600° C. for 5 h to obtain the semi-finished catalyst E;

[0065] (3) Weigh 17.32 mg of palladium nitrate and dissolve it in 45 ml of deionized water, add 15.52 g of n-hexane, 4.66 g of CTAB, and 3.88 g of n-pentanol, stir well to form a microemulsion, impregnate the semi-finished catalyst E into the prepared microemulsion, dry at 100° C. after the emulsion is completely absorbed, and calcine at 500° C. for 4 hours to obtain the semi-finished catalyst F;

[0066] (4) Weigh 21.65 mg of palladium nitrate and dissolve it in 45 g of deionized water. Adjust the pH to 1.6. Then add the semi-finished catalyst F to the Pd salt solution, age it for 10 hours, dry it at 120° C., and calcine it at 500° C. for 4 hours to obtain the desired catalyst.

[0067] The particle size of the microemulsion prepared in steps (2) and (3) was 200 nm as measured by dynamic light scattering.

[0068] The prepared catalyst was measured by atomic absorption spectrometry, and calculated based on the carrier as 100%, in Example 2, the Pd content was 0.018%, the Ni content was 1.6%, and the Fe content was 0.8%. The Pd content of the solution method was 0.01%, and the Pd content of the emulsion method was 0.008%.

[0069] Before use, it was placed in a fixed bed reaction device and reduced with a mixed gas with a molar ratio of N2:H2=1:1 at 220°C for 12 hours.

[0070] Comparative Example 2 provides a catalyst having the same carrier as that used in Example 2 and the same catalyst preparation conditions as those in Example 2, except that Fe is not loaded in the solution method in Comparative Example 2.

[0071] Catalyst preparation:

[0072] (1) Take 3.54 g of nickel chloride, dissolve it in 45 ml of deionized water, add 15.52 g of n-hexane, 4.66 g of CTAB, and 3.88 g of n-pentanol, stir well to form a microemulsion, and impregnate 100 g of the calcined support into the prepared microemulsion. After the emulsion is completely absorbed, dry it at 100° C. and calcine it at 600° C. for 5 h to obtain the semi-finished catalyst D1.

[0073] (2) Weigh 17.32 mg of palladium nitrate and dissolve it in 45 ml of deionized water, add 15.52 g of n-hexane, 4.66 g of CTAB, and 3.88 g of n-pentanol, stir well to form a microemulsion, and impregnate the semi-finished catalyst F into the prepared microemulsion. After the emulsion is completely absorbed, dry it at 100° C., and calcine it at 500° C. for 4 hours to obtain the semi-finished catalyst E1;

[0074] (3) Weigh 21.65 mg of palladium nitrate and dissolve it in 45 g of deionized water, adjust the pH to 1.6, then add the semi-finished catalyst E1 to the Pd salt solution, age it for 10 hours, dry it at 120°C, and calcine it at 500°C for 4 hours to obtain the desired catalyst.

[0075] The particle size of the microemulsion prepared in steps (1) and (2) was 200 nm as measured by dynamic light scattering.

[0076] The prepared catalyst was measured by atomic absorption spectrometry, and calculated based on the carrier as 100%, in Example 2, the Pd content was 0.018%, and the Ni content was 1.6%. The Pd content of the solution method was 0.01%, and the Pd content of the emulsion method was 0.008%.

[0077] Before use, it was placed in a fixed bed reaction device and reduced with a mixed gas with a molar ratio of N2:H2=1:1 at 220°C for 12 hours.

[0078] Example 3

[0079] Carrier: A commercially available bimodal pore distribution spherical carrier with a diameter of 4 mm and a composition of 80% alumina and 20% magnesium oxide was used. After calcination at 1250°C, the specific surface area was 15 m 2 / g, water absorption rate 51%, small pore diameter 30 ~ 55nm, large pore diameter 130 ~ 520nm, weigh 100g of the carrier.

[0080] Catalyst preparation:

[0081] (1) 7.78 g of nickel nitrate was weighed and dissolved in 51 ml of deionized water. 20.4 g of n-hexane, 8.16 g of CTAB and 5.83 g of n-pentanol were added and stirred thoroughly to form a microemulsion. 100 g of the carrier was impregnated into the prepared microemulsion. After the emulsion was completely absorbed, the carrier was calcined at 400° C. for 7 h to obtain a semi-finished catalyst H.

[0082] (2) Weigh 2.17 g of ferric nitrate and dissolve it in 51 g of deionized water, then add the semi-finished catalyst H to the prepared Fe salt solution, and after the solution is completely absorbed, age it for 6 hours, dry it at 120° C., and calcine it at 300° C. for 6 hours to obtain a semi-finished catalyst J;

[0083] (3) Weigh 20 mg of palladium chloride and dissolve it in 51 g of deionized water, adjust the pH to 2.0, then add the semi-finished catalyst J to the Pd salt solution, age it for 10 hours, dry it at 120° C., and calcine it at 550° C. for 4 hours to obtain the semi-finished catalyst K;

[0084] (4) Weigh 27.06 mg of palladium nitrate and dissolve it in 51 ml of deionized water. Add 20.4 g of n-hexane, 8.16 g of CTAB, and 5.83 g of n-pentanol, and stir well to form a microemulsion. Then, impregnate the semi-finished catalyst K into the prepared microemulsion. After immersion for 2 hours, wash it with deionized water until it is neutral, dry it at 60°C, and calcine it at 400°C for 6 hours to obtain the desired catalyst.

[0085] The particle size of the microemulsion prepared in steps (1) and (4) was determined to be 80 nm by dynamic light scattering.

[0086] The prepared catalyst was measured by atomic absorption spectrometry, and calculated based on the carrier as 100%, in Example 3, the Pd content was 0.0245%, the Ni content was 2.5%, and the Fe content was 0.5%. The Pd content loaded by the solution method was 0.012%, and the Pd content loaded by the emulsion method was 0.0125%.

[0087] Before use, it was placed in a fixed bed reaction device and reduced with a mixed gas with a molar ratio of N2:H2=1:1 at 180°C for 12 hours.

[0088] Comparative Example 3 provides a catalyst, wherein the carrier is the same as that of Example 3 and the preparation conditions are the same, except that in Comparative Example 3, Pd is first loaded by the emulsion method.

[0089] Catalyst preparation:

[0090] (1) Weigh 27.06 mg of palladium nitrate and dissolve it in 51 ml of deionized water. Add 20.4 g of n-hexane, 8.16 g of CTAB, and 5.83 g of n-pentanol, and stir thoroughly to form a microemulsion. Impregnate 100 g of the calcined support into the prepared microemulsion. After the emulsion is completely absorbed, dry it at 60° C. and calcine it at 400° C. for 6 hours to obtain a semi-finished catalyst H1.

[0091] (2) Weigh 2.17 g of ferric nitrate and dissolve it in 51 g of deionized water, then add the semi-finished catalyst H1 to the prepared Fe salt solution, and after the solution is completely absorbed, age it for 6 hours, dry it at 120° C., and calcine it at 300° C. for 6 hours to obtain the semi-finished catalyst J1;

[0092] (3) Weigh 20 mg of palladium chloride and dissolve it in 51 g of deionized water, adjust the pH to 2.0, then add the semi-finished catalyst J1 to the Pd salt solution, age it for 10 hours, dry it at 120° C., and calcine it at 550° C. for 4 hours to obtain the semi-finished catalyst K1;

[0093] (4) 7.78 g of nickel nitrate was dissolved in 51 ml of deionized water, and 20.4 g of n-hexane, 8.16 g of CTAB, and 5.83 g of n-pentanol were added and stirred thoroughly to form a microemulsion. 100 g of the carrier was impregnated into the prepared microemulsion. After the emulsion was completely absorbed, the carrier was calcined at 400°C for 7 h to obtain the desired catalyst.

[0094] The particle size of the microemulsion prepared in steps (1) and (4) was determined to be 80 nm by dynamic light scattering.

[0095] The prepared catalyst was measured by atomic absorption spectrometry, and calculated based on the carrier as 100%, in Example 3, the Pd content was 0.0245%, the Ni content was 2.5%, and the Fe content was 0.5%. The Pd content loaded by the solution method was 0.012%, and the Pd content loaded by the emulsion method was 0.0125%.

[0096] Before use, it was placed in a fixed bed reaction device and reduced with a mixed gas with a molar ratio of N2:H2=1:1 at 180°C for 12 hours.

[0097] Example 4

[0098] Carrier: A commercially available bimodal pore distribution spherical alumina carrier with a diameter of 3 mm was used. After calcination at 1330°C for 4 hours, the specific surface area was 7 m 2 / g, water absorption rate 48%, small pore diameter 50-70nm, large pore diameter 350-680nm, weigh 100g of the carrier.

[0099] Catalyst preparation:

[0100] (1) 4.67 g of nickel nitrate was dissolved in 40 ml of deionized water, and 10 g of cyclohexane, 1.6 g of Triton X-100, and 1.23 ml of n-butanol were added and stirred thoroughly to form a microemulsion. 100 g of the carrier was impregnated into the prepared microemulsion. After the microemulsion was completely absorbed, it was dried at 120° C. for 6 hours and calcined at 550° C. for 3 hours to obtain a semi-finished catalyst M.

[0101] (2) Weigh 6.52 g of ferric nitrate and dissolve it in 48 g of deionized water, then add the semi-finished catalyst M to the prepared Fe salt solution, and after the solution is completely absorbed, age it for 1 hour, dry it at 100° C., and calcine it at 350° C. for 8 hours to obtain the semi-finished catalyst N;

[0102] (3) 13.33 mg of palladium chloride was weighed and dissolved in 48 g of deionized water, and the pH was adjusted to 2.2. The semi-finished catalyst N was then added to the prepared Pd salt solution, aged for 12 hours, dried at 100° C., and calcined at 450° C. for 6 hours to obtain the semi-finished catalyst O;

[0103] (4) Weigh 8.33 mg of palladium chloride and dissolve it in 40 ml of deionized water. Add 10 g of cyclohexane, 1.6 g of Triton X-100, and 1.6 g of n-butanol. Stir thoroughly to form a microemulsion. Impregnate the semi-finished catalyst O into the prepared microemulsion. After immersion for 4 hours, filter out the remaining liquid; wash with deionized water until neutral, dry at 120° C. for 6 hours, and calcine at 450° C. for 6 hours to obtain the desired catalyst.

[0104] The particle size of the microemulsion prepared in steps (1) and (4) was 400 nm as measured by dynamic light scattering.

[0105] The prepared catalyst was measured by atomic absorption spectrometry, and calculated based on the carrier as 100%, in Example 4, the Pd content was 0.013%, the Ni content was 1.5%, and the Fe content was 1.5%. The Pd content loaded by the solution method was 0.008%, and the Pd content loaded by the emulsion method was 0.005%.

[0106] Before use, it was placed in a fixed bed reaction device and reduced with a mixed gas with a molar ratio of N2:H2=1:1 at 220°C for 12 hours.

[0107] Comparative Example 4 Comparative Example 4 provides a catalyst using the same carrier as in Example 4. The catalyst preparation conditions are also the same, except that the emulsion method does not load Pd.

[0108] Catalyst preparation:

[0109] (1) 4.67 g of nickel nitrate was dissolved in 40 ml of deionized water, and 10 g of cyclohexane, 1.6 g of Triton X-100, and 1.23 ml of n-butanol were added and stirred thoroughly to form a microemulsion. 100 g of the carrier was impregnated into the prepared microemulsion. After the microemulsion was completely absorbed, it was dried at 120° C. for 6 hours and calcined at 550° C. for 3 hours to obtain a semi-finished catalyst M.

[0110] (2) Weigh 6.52 g of ferric nitrate and dissolve it in 48 g of deionized water, then add the semi-finished catalyst M to the prepared Fe salt solution, and after the solution is completely absorbed, age it for 1 hour, dry it at 100° C., and calcine it at 350° C. for 8 hours to obtain the semi-finished catalyst N;

[0111] (3) Weigh 13.33 mg of palladium chloride and dissolve it in 48 g of deionized water. Adjust the pH to 2.2. Then add the semi-finished catalyst N to the prepared Pd salt solution. Aged for 12 hours, dried at 100° C., and calcined at 450° C. for 6 hours to obtain the desired catalyst.

[0112] The particle size of the microemulsion prepared in step (1) was determined to be 400 nm by dynamic light scattering.

[0113] The prepared catalyst was measured by atomic absorption spectrometry. Calculated based on the carrier as 100%, in Comparative Example 4, the Pd content was 0.008%, the Ni content was 1.5%, and the Fe content was 1.5%.

[0114] Before use, it was placed in a fixed bed reaction device and reduced with a mixed gas with a molar ratio of N2:H2=1:1 at 220°C for 12 hours.

[0115] Example 5

[0116] Carrier: A commercially available bimodal pore distribution spherical alumina carrier is used, with an alumina content of 95%, a titanium oxide content of 5%, and a diameter of 3.5 mm. After calcination at 1310, the specific surface area is 10m 2 / g, water absorption rate 44%, small pore diameter 40-65nm, large pore diameter 390-540nm, weigh 100g of the carrier. After high temperature roasting for 4h, weigh 100g of the carrier.

[0117] Catalyst preparation:

[0118] (1) Weigh 4.42 g of nickel chloride, dissolve it in 40 ml of deionized water, add 15.38 g of cyclohexane, 5.38 g of Triton X-10, and 3.85 g of n-butanol, stir thoroughly to form a microemulsion, impregnate 100 g of the carrier into the prepared microemulsion, dry at 120° C. for 6 hours after the emulsion is completely absorbed, and calcine at 450° C. for 5 hours to obtain a semi-finished catalyst P.

[0119] (2) Weigh 5.22 g of ferric nitrate and dissolve it in 44 g of deionized water, then add the semi-finished catalyst P to the prepared Fe salt solution, and after the solution is completely absorbed, age it for 4 hours, dry it at 110° C., and calcine it at 600° C. for 2 hours to obtain the semi-finished catalyst Q;

[0120] (3) Weighing 16.67 mg of palladium chloride and dissolving it in 44 g of deionized water, adjusting the pH to 1.9, then adding the semi-finished catalyst Q to the prepared Pd salt solution, aging for 12 hours after the solution is completely absorbed, drying at 100° C., and calcining at 400° C. for 8 hours to obtain the semi-finished catalyst R;

[0121] (4) Weigh 17.32 mg of palladium nitrate and dissolve it in 40 ml of deionized water. Add 15.38 g of cyclohexane, 5.38 g of Triton X-10, and 3.85 g of n-butanol to the 40 ml of deionized water and stir thoroughly to form a microemulsion. Impregnate the semi-finished catalyst R into the prepared microemulsion. After the emulsion is completely absorbed, dry it at 120° C. for 6 hours and calcine it at 480° C. for 6 hours to obtain the desired catalyst.

[0122] The particle size of the microemulsion prepared in steps (1) and (4) was 100 nm as measured by dynamic light scattering.

[0123] The prepared catalyst was measured by atomic absorption spectrometry, and calculated based on the carrier as 100%, in Example 5, the Pd content was 0.018%, the Ni content was 2.0%, and the Fe content was 1.2%. The Pd content of the solution method was 0.008%, and the Pd content of the emulsion method was 0.010%.

[0124] Before use, it was placed in a fixed bed reaction device and reduced with a mixed gas with a molar ratio of N2:H2=1:1 at 190°C for 12 hours.

[0125] Comparative Example 5

[0126] The same carrier and catalyst preparation process as in Example 5 were used, except that the particle size of the microemulsion in step (4) was different.

[0127] Catalyst preparation:

[0128] (1) Weigh 4.42 g of nickel chloride, dissolve it in 40 ml of deionized water, add 15.38 g of cyclohexane, 5.38 g of Triton X-10, and 3.85 g of n-butanol, stir thoroughly to form a microemulsion, impregnate 100 g of the carrier into the prepared microemulsion, dry at 120° C. for 6 hours after the emulsion is completely absorbed, and calcine at 450° C. for 5 hours to obtain a semi-finished catalyst P.

[0129] (2) Weigh 5.22 g of ferric nitrate and dissolve it in 44 g of deionized water, then add the semi-finished catalyst P to the prepared Fe salt solution, and after the solution is completely absorbed, age it for 4 hours, dry it at 110° C., and calcine it at 600° C. for 2 hours to obtain the semi-finished catalyst Q;

[0130] (3) Weighing 16.67 mg of palladium chloride and dissolving it in 44 g of deionized water, adjusting the pH to 1.9, then adding the semi-finished catalyst Q to the prepared Pd salt solution, aging for 12 hours after the solution is completely absorbed, drying at 100° C., and calcining at 400° C. for 8 hours to obtain the semi-finished catalyst R;

[0131] (4) Weigh 17.32 mg of palladium nitrate and dissolve it in 40 ml of deionized water. Add 9.52 g of cyclohexane, 1.14 g of Triton X-10, and 0.816 g of n-butanol to the 40 ml of deionized water and stir thoroughly to form a microemulsion. Impregnate the semi-finished catalyst R into the prepared microemulsion. After the emulsion is completely absorbed, dry it at 120° C. for 6 hours and calcine it at 480° C. for 6 hours to obtain the desired catalyst.

[0132] The particle size of the microemulsion prepared in step (1) was 100 nm as determined by dynamic light scattering. The particle size of the microemulsion prepared in step (4) was 700 nm.

[0133] The prepared catalyst was measured by absorption spectroscopy, and calculated based on the carrier as 100%, in Comparative Example 5, the Pd content was 0.018%, the Ni content was 2.0%, and the Fe content was 1.2%. The Pd content loaded by the solution method was 0.008%, and the Pd content loaded by the emulsion method was 0.010%.

[0134] Before use, it was placed in a fixed bed reaction device and reduced with a mixed gas with a molar ratio of N2:H2=1:1 at 190°C for 12 hours.

[0135] Example 6

[0136] Carrier: A commercially available bimodal pore distribution spherical carrier with a diameter of 4 mm was used. After calcination at 1325°C, the specific surface area was 12 m 2 / g, water absorption rate 47%, small pore diameter 40-60nm, large pore diameter 200-580nm, weigh 100g of the carrier.

[0137] Catalyst preparation:

[0138] (1) Weigh 2.92 g of ferric chloride and dissolve it in 47 g of deionized water. Then, weigh 100 g of the carrier and add it to the prepared Fe salt solution. After the solution is completely absorbed, age it for 6 hours, dry it at 120° C., and calcine it at 250° C. for 8 hours to obtain a semi-finished catalyst S.

[0139] (2) Weigh 3.11 g of nickel nitrate, dissolve it in 40 ml of deionized water, add 15.38 g of n-hexane, 6.15 g of CTAB, and 5.59 g of n-octanol, stir well to form a microemulsion, and then immerse the semi-finished catalyst S in the prepared microemulsion. After the emulsion is completely absorbed, dry it at 80° C. and calcine it at 400° C. for 8 h to obtain the semi-finished catalyst T;

[0140] (3) Weigh 25 mg of palladium chloride and dissolve it in 47 g of deionized water, adjust the pH to 2.5, then add the semi-finished catalyst T to the Pd salt solution, age it for 10 hours, dry it at 120° C., and calcine it at 420° C. for 4 hours to obtain the semi-finished catalyst U;

[0141] (4) Weigh 11.17 mg of palladium chloride and dissolve it in 40 ml of deionized water. Add 15.38 g of n-hexane, 6.15 g of CTAB, and 5.59 g of n-octanol, and stir well to form a microemulsion. Then, impregnate the semi-finished catalyst U into the prepared microemulsion. After the emulsion is completely absorbed, dry it at 80° C. and calcine it at 520° C. for 4 hours to obtain the desired catalyst.

[0142] The particle size of the microemulsion prepared in steps (2) and (4) was 200 nm as measured by dynamic light scattering.

[0143] The prepared catalyst was measured by atomic absorption spectrometry, and calculated based on the carrier as 100%, in Example 6, the Pd content was 0.0217%, the Ni content was 1.0%, and the Fe content was 1.0%. The Pd content loaded by the solution method was 0.015%, and the Pd content loaded by the emulsion method was 0.0067%.

[0144] Before use, it was placed in a fixed bed reactor and reduced with pure hydrogen at 200°C for 8 hours.

[0145] Comparative Example 6 provides a catalyst whose carrier is the same as that of Example 6 and the catalyst preparation conditions are the same, except that Pd is loaded first and then Fe is loaded in the solution method.

[0146] Catalyst preparation:

[0147] (1) Weigh 25 mg of palladium chloride and dissolve it in 47 g of deionized water, adjust the pH to 2.5, add 100 g of the carrier to the Pd salt solution, and after the solution is completely absorbed, dry at 120° C. and calcine at 420° C. for 4 hours to obtain a semi-finished catalyst S1.

[0148] (2) Weigh 3.11 g of nickel nitrate, dissolve it in 40 ml of deionized water, add 15.38 g of n-hexane, 6.15 g of CTAB, and 5.59 g of n-octanol, stir well to form a microemulsion, and then immerse the semi-finished catalyst S1 in the prepared microemulsion. After the emulsion is completely absorbed, dry it at 80° C. and calcine it at 400° C. for 8 h to obtain the semi-finished catalyst T1;

[0149] (3) Weigh 2.92 g of ferric chloride and dissolve it in 47 g of deionized water, then add the semi-finished catalyst T to the prepared Fe salt solution and age it for 10 hours, age it for 6 hours, dry it at 120° C., and calcine it at 250° C. for 8 hours to obtain the semi-finished catalyst U1;

[0150] (4) Weigh 11.17 mg of palladium chloride, dissolve it in 40 ml of deionized water, add 15.38 g of n-hexane, 6.15 g of CTAB, and 5.59 g of n-octanol, stir well to form a microemulsion, and impregnate the semi-finished catalyst U1 into the prepared microemulsion. After the emulsion is completely absorbed, dry it at 80° C. and calcine it at 520° C. for 4 hours to obtain the desired catalyst.

[0151] The particle size of the microemulsion prepared in steps (2) and (4) was 200 nm as measured by dynamic light scattering.

[0152] The prepared catalyst was measured by atomic absorption spectrometry, and calculated based on the carrier as 100%, in Example 6, the Pd content was 0.0217%, the Ni content was 1.0%, and the Fe content was 1.0%. The Pd content loaded by the solution method was 0.015%, and the Pd content loaded by the emulsion method was 0.0067%.

[0153] Before use, it was placed in a fixed bed reactor and reduced with pure hydrogen at 200°C for 8 hours.

[0154] Example 7

[0155] Carrier: A commercially available bimodal pore distribution spherical alumina carrier with a diameter of 4 mm was used. After calcination at 1310°C, the specific surface area was 12 m 2 / g, water absorption rate 46%, small pore diameter 40 ~ 60nm, large pore diameter 200 ~ 580nm, weigh 100g of the carrier

[0156] Catalyst preparation:

[0157] (1) 7.47 g of nickel nitrate was weighed and dissolved in 42 ml of deionized water. 12 g of n-hexane, 3.24 g of CTAB, and 2.95 g of n-pentanol were added and stirred thoroughly to form a microemulsion. 100 g of the carrier was impregnated into the prepared microemulsion for 0.5 hour, and then washed with deionized water until neutral, dried at 80° C., and calcined at 400° C. for 8 hours to obtain a semi-finished catalyst V.

[0158] (2) Weigh 6.52 g of ferric nitrate and dissolve it in 47 g of deionized water, then add the semi-finished catalyst V to the prepared Fe salt solution, and after the solution is completely absorbed, age it for 6 hours, dry it at 120° C., and calcine it at 400° C. for 8 hours to obtain the semi-finished catalyst W;

[0159] (3) 13.33 mg of palladium chloride was weighed and dissolved in 47 g of deionized water, and the pH was adjusted to 2.3. The semi-finished catalyst W was then added to the Pd salt solution, aged for 10 hours, dried at 120° C., and calcined at 530° C. for 4 hours to obtain the semi-finished catalyst X;

[0160] (4) Weigh 12.99 mg of palladium nitrate and dissolve it in 42 ml of deionized water. Add 12 g of n-hexane, 3.24 g of CTAB, and 2.95 g of n-pentanol. Stir well to form a microemulsion. Then, impregnate the semi-finished catalyst X into the prepared microemulsion. After immersion for 0.5 hour, wash with deionized water until neutral, dry at 80° C., and calcine at 520° C. for 4 hours to obtain the desired catalyst.

[0161] The particle size of the microemulsion prepared in steps (1) and (4) was 200 nm as measured by dynamic light scattering.

[0162] The prepared catalyst was measured by atomic absorption spectrometry, and calculated based on the carrier as 100%, in Example 6, the Pd content was 0.016%, the Ni content was 2.4%, and the Fe content was 2.0%. The Pd content loaded by the solution method was 0.008%, and the Pd content loaded by the emulsion method was 0.008%.

[0163] Before use, it was placed in a fixed bed reactor and reduced with pure hydrogen at 210°C for 8 hours.

[0164] Comparative Example 7 This comparative example provides a catalyst whose carrier is the same as that in Example 7 and the catalyst preparation conditions are the same, except that in Comparative Example 7, Pd is first loaded by the emulsion method.

[0165] (1) Weigh 12.99 mg of palladium nitrate, dissolve it in 42 ml of deionized water, add 12 g of n-hexane, 3.24 g of CTAB, and 2.95 g of n-pentanol, stir well to form a microemulsion, and impregnate 100 g of the carrier into the prepared microemulsion. After the emulsion is completely absorbed, dry it at 80° C. and calcine it at 520° C. for 4 hours to obtain a semi-finished catalyst V1.

[0166] (2) Weigh 6.52 g of ferric nitrate and dissolve it in 47 g of deionized water, then add the semi-finished catalyst V1 to the prepared Fe salt solution, and after the solution is completely absorbed, age it for 6 hours, dry it at 120° C., and calcine it at 400° C. for 8 hours to obtain the semi-finished catalyst W1;

[0167] (3) Weigh 13.33 mg of palladium chloride and dissolve it in 47 g of deionized water, adjust the pH to 2.3, then add the semi-finished catalyst W1 into the Pd salt solution, age it for 10 hours, dry it at 120° C., and calcine it at 530° C. for 4 hours to obtain the semi-finished catalyst X1;

[0168] (4) Weigh 7.47 g of nickel nitrate and dissolve it in 42 ml of deionized water. Add 12 g of n-hexane, 3.24 g of CTAB, and 2.95 g of n-pentanol, and stir thoroughly to form a microemulsion. Impregnate the semi-finished catalyst X1 into the prepared microemulsion. After the emulsion is completely absorbed, dry it at 80° C. and calcine it at 400° C. for 8 h to obtain the desired catalyst.

[0169] The particle size of the microemulsion prepared in steps (1) and (4) was 200 nm as measured by dynamic light scattering.

[0170] The prepared catalyst was measured by atomic absorption spectrometry, and calculated based on the carrier as 100%, in Example 6, the Pd content was 0.016%, the Ni content was 2.4%, and the Fe content was 2.0%. The Pd content loaded by the solution method was 0.008%, and the Pd content loaded by the emulsion method was 0.008%.

[0171] Before use, it was placed in a fixed bed reactor and reduced with pure hydrogen at 210°C for 8 hours.

[0172] Example 8

[0173] Carrier: A commercially available bimodal pore distribution spherical alumina carrier with a diameter of 3.5 mm, calcined at 110 ° C, with a specific surface area of ​​10 m 2 / g, water absorption rate 45%, small pore diameter 50-70nm, large pore diameter 300-650nm, weigh 100g of the carrier.

[0174] (1) Weigh 2.33 g of ferric chloride and dissolve it in 45 g of deionized water. Add 100 g of the calcined carrier to the prepared Fe salt solution. After the solution is completely absorbed, age it for 4 hours, dry it at 100° C., and calcine it at 280° C. for 6 hours to obtain a semi-finished catalyst AA.

[0175] (2) 6.23 g of nickel nitrate was dissolved in 45 ml of deionized water, and 17.31 g of n-hexane, 6.06 g of CTAB, and 4.33 g of n-octanol were added and stirred to form a microemulsion. The semi-finished catalyst AA was impregnated into the prepared microemulsion, and after the emulsion was completely absorbed, it was dried at 100° C. and calcined at 520° C. for 5 h to obtain the semi-finished catalyst AB;

[0176] (3) Weigh 10.82 mg of palladium nitrate and dissolve it in 45 g of deionized water, adjust the pH to 1.6, then add the semi-finished catalyst AB to the Pd salt solution, age for 10 hours, dry at 60° C., and calcine at 480° C. for 4 hours to obtain the semi-finished catalyst AC;

[0177] (4) Weigh 32.47 mg of palladium nitrate and dissolve it in 45 ml of deionized water. Add 17.31 g of n-hexane, 6.06 g of CTAB, and 4.33 g of n-octanol, and stir thoroughly to form a microemulsion. Impregnate the semi-finished catalyst AC into the prepared microemulsion. After the emulsion is completely absorbed, dry it at 80°C, and calcine it at 420°C for 4 hours to obtain the desired catalyst.

[0178] The particle size of the microemulsion prepared in steps (2) and (4) was 100 nm as measured by dynamic light scattering.

[0179] The prepared catalyst was measured by atomic absorption spectrometry, and calculated based on the carrier as 100%, in Example 2, the Pd content was 0.020%, the Ni content was 2.0%, and the Fe content was 0.8%. The Pd content loaded by the solution method was 0.015%, and the Pd content loaded by the emulsion method was 0.005%.

[0180] Performance of catalysts for C2 post-hydrogenation

[0181] Evaluation test 1: Reaction conditions: The catalyst loading amount in the fixed bed single-stage reactor is 100 mL, the reaction material space velocity: 10000 / h, the operating pressure: 3.4 MPa, and the initial inlet temperature of the reactor is 100°C.

[0182] Reaction requirements: first-stage acetylene conversion rate above 65%, selectivity above 80%.

[0183] The composition of the reaction materials is shown in Table 1.

[0184] Table 1 Reaction material composition

[0185]

[0186] Table 2 Catalyst evaluation results

[0187]

[0188] Compared with Example 1, Comparative Example 1 does not have Ni loaded in the comparative example, and the catalyst macropores have basically no hydrogenation function for the hydrogenation byproduct butadiene. After 1000 hours, the activity selectivity decreases significantly.

[0189] In Comparative Example 2, no Fe is loaded, and only a very small amount of Pd is contained in the small pores, and the acetylene hydrogenation activity thereof is very low.

[0190] In Comparative Example 3, the solution method did not load Pd, and Fe had very low activity at this content because its ability to adsorb hydrogen was poor, resulting in a significant difference in acetylene conversion rate from that in the example.

[0191] In Comparative Example 4, Pd was not loaded in the microemulsion method. At a temperature of about 200°C, Ni was not effectively reduced and could not effectively perform the role of saturated hydrogenation of the reaction by-products. It is possible that only a small amount of by-products underwent saturated hydrogenation on the surface of the Pd active center. The amount of catalyst coking was significantly higher than that of the embodiment. The selectivity of the catalyst in the comparative example decreased by 5 percentage points after 1000 hours, and the selectivity decreased by 9 percentage points, while the selectivity of the catalyst in embodiment 4 only decreased by 1 percentage point. That is to say, the deactivation rate of the catalyst in comparative example 4 is 9 times that of the catalyst in embodiment 4.

[0192] In Comparative Example 5, the particle size of the microemulsion when loaded with Pd is larger than the maximum pore size of the macropores of the carrier, and the microemulsion cannot effectively enter the macropores, and is only loaded on the outermost surface of the catalyst, partially playing a role in acetylene hydrogenation, or reacting with Ni to play a role in saturated hydrogenation of a small amount of byproducts. After 1000 hours, the activity and selectivity are significantly lower than those of Example 5. Since the Pd loaded by the microemulsion is located on the outer surface of the catalyst, although the Fe loading in Comparative Example 5 is significantly lower than that in Comparative Example 4, its initial acetylene hydrogenation activity is equivalent to that of Comparative Example 4.

[0193] In Comparative Example 6, Pd is first loaded by the solution method. This small amount of Pd is covered by the later loaded Fe and cannot provide hydrogen for the Fe active center in the reaction. The activity of acetylene hydrogenation is very low.

[0194] In Comparative Example 7, the Pd first loaded by the emulsion method is covered by the Ni loaded later by the emulsion method, and it cannot effectively reduce the Ni reduction temperature, and the saturated hydrogenation reaction of the by-products cannot occur. The catalyst selectivity decrease rate is much faster than that of the catalyst in Example 7.

[0195] In Comparative Example 8, the specific surface area of ​​the carrier is 2 times higher than that of Example 8, and the area of ​​the active component loading is much higher than that of the Example, resulting in insufficient activity of the two active centers in the catalyst of the comparative example, which makes the initial conversion rate of acetylene low, and the activity of the saturated hydrogenation center is insufficient, resulting in a faster decrease in activity selectivity after 1000 hours than that of the Example.

[0196] Evaluation test 2

[0197] The test sample is the catalyst of Example 8.

[0198] Material composition: Same as Experiment 1, except that CO was added alone, and the rate of change of its content was from 0.04% (v) to 0.15% (v) within 15 min.

[0199] Sampling and analysis method: Analyze once before adjusting the CO content, analyze once after the CO content adjustment, and perform a second sampling and analysis after 15 minutes.

[0200] Reaction conditions: The catalyst loading amount in the fixed bed two-stage reactor is 300 mL, the catalyst reaction material space velocity is 12000 / h, the operating pressure is 3.6 MPa, the initial inlet temperature of the reactor is 105°C, and the second stage temperature is 120°C.

[0201] The evaluation results are shown in Table 3.

[0202] Table 3 Reaction material composition and evaluation results

[0203]

[0204] From the results in Table 3, it can be seen that when the contents of other components in the hydrogenation material remain basically unchanged, CO is increased from 0.05% (v) to 0.15% (v) within 15 minutes, and the content is increased by 2 times, almost from the lowest content to the highest content, which is also the maximum limit that can be achieved by industrial equipment. Before the CO content is increased, the conversion rate of acetylene in the first stage is 92.4%, and the acetylene in the second stage is completely converted; after the CO content is increased, the conversion rate of acetylene in the first stage is reduced by 10 percentage points, and the selectivity is increased by 4 percentage points; the conversion rate of acetylene in the second stage is still 100%. The test was conducted again after 15 minutes, and the result was equivalent to the first analysis result after the CO change.

[0205] The results show that the rapid and substantial increase in CO content does have an impact on the hydrogenation activity of the first stage catalyst of the present invention, but the change range is very small compared to the noble metal catalyst, and the second stage can still completely convert acetylene, indicating that even if CO reaches almost the maximum change range, the catalyst of the present invention can still achieve the effect of no acetylene leakage. This is a prominent advantage over traditional catalysts.

Claims

1. A selective hydrogenation catalyst for C1-C3 fractions, wherein the catalyst carrier has a bimodal pore distribution structure, characterized in that: The catalyst contains at least Pd, Ni and Fe; wherein Pd is loaded by a microemulsion method and a solution method; Ni is loaded by a microemulsion method; and Fe is loaded by a solution method; based on the mass of the carrier being 100%, the total content of Pd loaded by the microemulsion method and the solution method is 0.009-0.0245%, wherein the content of Pd loaded by the solution method is 0.007-0.015%, and the ratio of Pd loaded by the solution method to Fe loaded by the solution method is 0.004-0.024:1; the content of Ni is 1.0-2.5%; and the content of Fe is 0.5-1.5%.

2. The selective hydrogenation catalyst for C1-C3 fractions according to claim 1, characterized in that: In the bimodal pore distribution structure, the diameter of the small pores is 30 to 80 nm, and the diameter of the large pores is 130 to 800 nm.

3. The selective hydrogenation catalyst for C1-C3 fractions according to claim 1, characterized in that: The specific surface area of ​​the catalyst is 3 to 15 m2 / g.

4. A method for preparing a selective hydrogenation catalyst for a C1 to C3 fraction according to any one of claims 1 to 3, characterized in that: In the method, nickel and iron are loaded first, and palladium is loaded later.

5. The method according to claim 4, characterized in that Nickel is loaded by a microemulsion method, iron is loaded by a solution method, and palladium is loaded by a microemulsion method and / or a solution method.

6. The method according to claim 5, characterized in that include: (1) adding the carrier to a Ni microemulsion for impregnation, calcining, and then adding an aqueous solution of an Fe precursor salt for impregnation and calcining; or, adding the carrier to an aqueous solution of an Fe precursor salt, calcining, and then adding the carrier to a Ni microemulsion for impregnation and calcining; the Ni microemulsion is formed by adding an oil phase, a surfactant, and a co-surfactant to an aqueous solution of a Ni precursor salt, and stirring, and the particle size of the microemulsion is greater than 80 nm and less than 800 nm; (2) adding the product prepared in step (1) to an aqueous solution of a Pd precursor salt, aging, drying, and calcining, and then adding a Pd microemulsion for impregnation and calcining; or, adding the product prepared in step (1) to a Pd microemulsion for impregnation and calcining, and then adding it to an aqueous solution of a Pd precursor salt for aging, drying, and calcining; the Pd microemulsion is formed by adding an oil phase, a surfactant, and a co-surfactant to an aqueous solution of a Pd precursor salt and stirring, and the particle size of the microemulsion is greater than 80 nm and less than 800 nm.

7. The method according to claim 6, characterized in that In step (1), the oil phase is alkane, the surfactant is Triton X-100 or CTAB, and the co-surfactant is alcohol.

8. The method of claim 7, characterized in that The oil phase in step (1) is cyclohexane or n-hexane, and the co-surfactant is n-butanol, n-pentanol or n-octanol.

9. The method of claim 6, characterized in that In step (2), the oil phase is alkane, the surfactant is Triton X-100 or CTAB, and the co-surfactant is alcohol.

10. The method according to claim 9, characterized in that The oil phase in step (2) is cyclohexane or n-hexane, and the co-surfactant is n-butanol, n-pentanol or n-octanol.

11. The method of claim 6, characterized in that In the step (1) and the step (2), the mass ratio of water in the aqueous solution to the oil phase is 2.5 to 4.5:1; the mass ratio of the surfactant to the oil phase is 0.1 to 0.4:1; and the mass ratio of the surfactant to the co-surfactant is 1.0 to 1.40:

1.

12. The method of claim 6, characterized in that The calcination temperature in step (1) is 400-600°C.

13. The method of claim 6, characterized in that The calcination temperature in step (2) is 250-600°C.

14. A process for hydrogenating carbon dioxide, characterized in that: Use the selective hydrogenation catalyst for the C1-C3 fraction according to any one of claims 1-3.

Citation Information

Patent Citations

  • Non-noble metal supported selective hydrogenation catalyst and preparation method and application thereof

    CN101664682A

  • Palladium-silver bimetallic hydrogenation catalyst

    CN102205243A

  • Selective hydrogenation catalyst for improving coking resistance

    CN104096572A

  • A preparation method of a highly coke-resistant selective hydrogenation catalyst

    CN104096573B

  • C2 fraction selective-hydrogenation method

    CN104098426A